Les réseaux de polygones à fissures de contraction thermique au Nunavik - Chiasson, Alexandre (Université Laval, 2019)
Despite abundant research in Nunavik on permafrost, ice-wedge polygons and ground thermal cracking, no study has yet been addressing the spatial distribution of active frost cracking and of thermal contraction crack polygons. To fill that knowledge gap, this study evaluates the spatial distribution of actively cracking polygons under the current climate conditions across the different bioclimatic zones of Nunavik. The study also assesses the importance of cold Holocene climate episodes for the formation of polygonal networks over the territory. Thousands of geo-referenced aerial photographs (80 737) and Esri satellite images (264,504.14 km²) were analyzed to conduct an extensive inventory of Nunavik's tundra polygons. A total of 4,567 polygonal networks were inventoried. For each identified site, the arrangement (e. g. open, closed or unorganized networks), intersections (angles), cracking orders (primary, secondary and tertiary cracks), type of bulge and rims (flat, high-centred, low-centred), the affected surficial geological materials and the vegetation cover were noted and compiled in a database. Mapping of the results and modelling of cracking conditions indicate that currently active polygonal networks are only present beyond 60°N, in the herbaceous tundra principally in organic soils, on raised beaches and on sandy organic-covered fluvial terraces. In addition, the statistical tests carried out on our sampled population showed that there is a strong dependency between the types of surficial deposits and the different angles forming the polygonal networks. Orthogonal polygons (90° intersection angles) dominate on flat terrains where the thermo-mechanical stresses are spatially homogenous and hexagonal polygons (120° intersection angles) are observed more likely on uneven terrain where local topography generates non-homogenous heat flows and uneven thermo-mechanical stresses in the ground, thus forcing a less regular cracking pattern Malgré d’abondantes recherches sur le pergélisol au Nunavik, les sols ...